Plasma levels of the soluble form of the FcγRIIa receptor vary with receptor polymorphisms and are elevated in rheumatoid arthritis. (2nd April 2020) - Qiao, Jianlin; Dunne, Eimear; Wines, Bruce; Kenny, Dermot; McCarthy, Geraldine M.; Hogarth, P. Mark; Xu, Kailin; Andrews, Robert K.; Gardiner, Elizabeth E.
Abstract: Soluble forms of the low-affinity immunoglobulin receptor FcγRIIa (sFcγRIIa) lacking the cytoplasmic tail have been reported in plasma however the mechanism and functional consequences are unknown. This study aimed to evaluate mechanisms of FcγRIIa release compared to GPVI release from platelets, and examine whether genetic polymorphisms at positions 27 and 131 within FcγRIIa correlate with platelet FcγRIIa stability and function. Enzyme-linked immunosorbent assays (ELISAs) were used to measure plasma sFcγRIIa and sGPVI levels. FcγRIIa genotype at positions 27 and 131 was evaluated. sFcγRIIa levels were not significantly different between non-131HH and 131HH but were significantly lower in 27W than non-27W. Treatment of platelets with aggregated immunoglobulin (Ig) G induced release of FcγRIIa and GPVI, but only sGPVI release was statistically significant, required functional FcγRIIa, and was blocked by inhibitors of signaling pathways and metalloproteinases. This indicated that sFcγRIIa was not released from platelets by metalloproteolysis. sFcγRIIa levels were not correlated with sGPVI levels in healthy individuals however levels of sFcγRIIa and sGPVI in plasma from patients with rheumatoid arthritis (RA) were significantly elevated above levels found in healthy individuals. Elevated level of sFcγRIIa in RA patients may reflect active immune-based arthritis and be predictive of active inflammation.